SOME METHODS TO EXPRESS VIETNAMESE WISHES IN COMMUNICATION (Journal of Foreign Language Studies, 2022)
This study adopts qualitative research methods to obtain data from oral and written communication and presents six methods of expressing wishes by Vietnamese people. The findings show that Vietnamese people use flexible methods of expressing wishes. A wish can be combined with other speech acts such as praise, thanks, greetings, regards, encouragements and reminders. A wish can also be included to enhance courtesy in spoken language and improve the effectiveness of communication. This study is expected to make contribution to research on wishes in languages in general and in the Vietnamese language in particular.
Keywords: wish; positive politeness; Vietnamese wishes